Remember:
a) (x,y) => (x, -y) is a reflection across X axis
b) (x,y) => (-x,y) is a reflection across Y axis
Here △RST is mapped to △R′S′T′ using the rule (x,y)→(x,−y)
Hence it is a reflection across X axis.
The size of the triangle does not alter.
But when this is followed by (x,y)→(3x,3y), the lengths increase by a factor 3.
Hence the triangles do not remain congruent.
△RST is not congruent to △R′S′T′ because the rules do not represent a sequence of rigid motions.
Option A) is the right answer